Students’ Perceptions of Excellence in Chilean High-Performing Public Schools - Quaresma, Maria Luísa; Allende, Claudio; Villalobos, Cristóbal; Araneda, Sebastián (Frontiers in Education, 2022)
This paper aims to analyze how students attending six of the most prestigious, selective, and high-performing public schools in Chile perceive the concept of excellence and what factors influence their perceptions. A survey was administered to 1,828 students enrolled in 11th and 12th grade. The results show that students share a multidimensional idea of excellence. Five dimensions are identified but, according to students’ perceptions, there were two constructs that stood out the most: ‘effort and self-improvement’ and ‘social commitment and thoughtfulness’. We find that variables such as expectations about the future and perceptions about schools explain the dissimilar ideas of excellence shared by students. This research gives voice to students on a current topic of the educational agenda –the concept of excellence– and invites researchers to re-think this construct from perspectives other than academic achievements.